Revitalisasi Kompleks Kavallerie Sebagai Hotel Heritage di Pura Mangkunegaran Surakarta - Sumirat, Arya Teja; , Dr. Ir. Qomarun, MM; , Ir. Samsudin Raidi, MSc (2015)
Revitalization of Complex Kavallerie As Heritage Hotel in Pura Mangkunegaran Surakarta is a legacy of development efforts in the form of complex Pura Mangkunegaran Kavallerie - Artillerie which still exists to this day, how a process, how, act revive or revitalize the building environment to stay that was formerly in the form of barracks for troops riding armored vehicles and troops belonging to Mangkunegaran, a dynasty originating from the Mataram dynasty that once ruled in Surakarta since 1757 up to 1946 to be a heritage hotel full of culture in Mangkunegaran own. The rationale on complex historical objects Kavallerie Mangkunegaran extinct is to revitalize Complex Kavallerie as tourism history by rebuilding Complex Kavallerie with different functions, namely as a Heritage Hotel. By analyzing the macro and micro. Namely macro Function Analysis and Strategy, Objectives and Scope and Limitations Region. While Micro namely Analysis and Concepts Site, Space, Mass, Display Architecture, Structure and Utilities and emphasis. Keywords: Revitalization, Complex Kavallerie Mangkunegaran, Hotel Heritage